Negative beliefs about breathlessness increases panic for patients with chronic respiratory disease. - Hallas, Claire N.; Howard, Claire; Theadom, Alice; Wray, Jo (Psychology, Health & Medicine, 2012)
Breathlessness is a multidimensional symptom of respiratory disease and is associated with the experience of panic. Patients with panic disorder have increased mortality, morbidity and healthcare utilisation that is unrelated to their disease severity. Our qualitative study aimed to appraise respiratory patients’ experiences of breathlessness and whether their cognitions were associated with panic aetiology. The Self-Regulatory Theory was utilised to develop the framework for the semi-structured interview schedule. Twelve individuals with respiratory disease at a UK cardiothoracic centre participated and their data were analysed using Interpretative Phenomenological Analysis. Perceived control over the disease, symptoms and panic emerged as the core theme with three related belief systems; (1) Perceived consequences of panic and disease; (2) Illness and symptom coherence; and (3) Emotional adaptation. Panic symptoms were most prevalent in participants with low perceived control over symptoms and the disease, negative beliefs about the life-limiting consequences of unpredictable breathless attacks and by those using emotional coping strategies such as denial and avoidance. The experience of panic for respiratory patients can be explained through the cognitive-behavioural model of anxiety, which highlights the contributory role of catastrophic beliefs about the control and consequences of symptoms and disease as a significant contributory factor for the prevalence and maintenance of panic. The mortality and morbidity of respiratory patients is significantly affected by a co-morbid diagnosis of panic disorder and so it is critical to patients’ long-term healthcare that their psychological experiences are assessed. Healthcare services must enhance patients’ understanding about their disease to improve their confidence to control symptoms. Recent evidence suggests that cognitive-behavioural interventions that increase problem-solving coping will reduce catastrophic misinterpretations about the perceived consequences of breathlessness and improve emotional adaption to respiratory disease.